Modeling and parameter importance investigation for simulating in-plane and out-of-plane behaviors of un-reinforced masonry walls. (1st December 2021) - Zeng, Bowen; Li, Yong; Cruz Noguez, Carlos
Highlights: A finite element modeling strategy for URM wall is presented based on contact-based cohesive surface. The presented finite element strategy can be used to as a unified approach to simulate brick–mortar-brick assemblages and URM wall under in-plane (IP) loading and out-of-plane (OOP) loading. Good agreement is reached in the numerical-experimental comparison. Parametric study is conducted to investigate importance of influencing material parameters on the URM behavior under IP and OOP loading, respectively. Abstract: The mechanical behavior of un-reinforced masonry (URM) walls is complex due to the masonry heterogeneity and anisotropy, and thus finite element (FE) prediction of their structural response under in-plane (IP) and/or out-of-plane (OOP) loading conditions remains a challenging task for engineers. In this paper, 3D FE models were developed in the commercial FE software Abaqus 2017 using off-the-shelf continuum elements for units and contact-based cohesive surfaces for between- or within-brick interfaces. This FE strategy was validated, as a unified modeling approach, which is capable of predicting the response of brick–mortar-brick assemblages and URM walls under IP and OOP loadings. The numerical-experimental comparisons showed the accuracy and potential of the FE models developed. A parametric study was then conducted to investigate the relative importance of influencing material parameters on the URM behavior under IP and OOP loadings. The results of parametric study indicated that the OOP behavior was affected by the tension-related interface parameters, while the IP behavior was affected by both shear-related and tension-related interface parameters.